Control of Plant Branching by the CUC2/CUC3-DA1-UBP15 Regulatory Module. Issue 6 (2nd April 2020) - Li, Yu; Xia, Tian; Gao, Fan; Li, Yunhai
Abstract : CUC2/CUC3, DA1, and UBP15 function in a common pathway to control the initiation of axillary meristems, thereby determining plant branching in Arabidopsis. Abstract: Lateral branches are important for plant architecture and production, but how plants determine their lateral branches remains to be further understood. Here, we report that the CUP-SHAPED COTYLEDON2 (CUC2)/CUC3-DA1-UBIQUITIN-SPECIFIC PROTEASE15 (UBP15) regulatory module controls the initiation of axillary meristems, thereby determining the number of lateral branches in Arabidopsis ( Arabidopsis thaliana ). Mutation in the ubiquitin-dependent peptidase DA1 causes fewer lateral branches due to defects in the initiation of axillary meristems. The transcription factors CUC2 and CUC3, which regulate the axillary meristem initiation, directly bind to the DA1 promoter and activate its expression. Further results show that UBP15, which is a direct substrate of DA1 peptidase, represses the initiation of axillary meristems. Genetic analyses support that CUC2/CUC3, DA1, and UBP15 function, at least in part, in a common pathway to regulate the initiation of axillary meristems. Therefore, our findings establish a genetic and molecular framework by which the CUC2/CUC3-DA1-UBP15 regulatory module controls the initiation of axillary meristems, thereby determining plant architecture.